An Improved Virtual Inertia Algorithm of Virtual Synchronous Generator - Haizhen Xu (Journal of Modern Power Systems and Clean Energy, 2020)
Virtual synchronous generator (VSG) simulates the first-order motion equation of a synchronous generator (SG) with the algorithm. VSG can improve the system voltage and frequency support capabilities of a microgrid or a weak grid. It is now widely applied at a high penetration level of distributed generation (DG) systems. However, because there is a contradiction between active power steady-state deviation of VSG and dynamic impact regulation, the VSG running in grid-connected mode with existing strategies cannot meet the steady and dynamic control requirements. Thus, an improved virtual inertial control strategy of VSG is proposed in this paper. The active power impact is reduced effectively under the circumstance of damping coefficient Dω equal to 0 and a large inertia, thus the dynamic characteristic of active power is improved and its steady-state characteristic is maintained. Firstly, based on the analysis of the damping coefficient effect on the system dynamic process, two forms of improved virtual inertia algorithms are put forward by cascading a differential link into different positions of the first-order virtual inertia forward channel. Then, by comparing the characteristics of the system with the two improved algorithms, the improved virtual inertial strategy based on differential compensation is proven to be better, and the design of its parameters is analyzed. Finally, simulation and experimental results verify the effectiveness of the proposed algorithm.